Efectos de producción de cuatro fórmulas de fertilizantes en plantaciones establecidas de cacao CC-N-51 - Trujillo Morillo, Feliciano (2012)
In the country property San Remus located to 10 km of the parish Port Lemon, Sacred Domingo from the Colorado; property of Mr. Eduard Evans. The geographical location is of 0º17'30 '' of north latitude and 75º20'22 '' of longitude west, located 660 m.s.n.m. This investigation had a duration of nine months. As main objective we have: To evaluate the effect of the application of four fertilizer formulas in the production of established plantations of cocoa DC-N-51. Under a design of blocks at random (DBCA) with four treatments and four repetitions, to the p <0.05% of probability. The treatments were evaluated: T1 = 10 - 30 - 10 kg/ha-1 (Witness) NPK; T2 = 12 - 12 - 17 - 2 kg/ha-1 Blue Nitrofosca; T3 = 15 - 5 - 20 - 2 kg/ha-1 lived Nitrofosca; T4 = 20 - 6 - 17 - 13 - 4 - 1 kg/ha-1 Ferticacao. The obtained results demonstrate that the Treatment T4 = 20 - 6 - 17 - 13 - 4 - 1 kg/ha-1 Ferticacao presents the best answers in the variable number and I release of ear with (38.00) and (31.20 cm), I weigh of the ear (631,70 g) and yield for hectare (3160,90 kg) or (69,67 qq) and the biggest profitability 0.53%. Keywords: Established plantations of cocoa DC-N-51; fertilizer; yield.